Kesantunan Berbicara Bahasa Jawa Siswa Kelas V Sekolah Dasar (Jurusan Bahasa dan Sastra Jawa Universitas Negeri Semarang, 2022)
This study aims to describe the forms of violation and compliance with students' language politeness when communicating using Javanese according to the level of Javanese speech and the principles of politeness. This type of research is a qualitative research using descriptive method. Data collection techniques used are questionnaires, observations, and interviews. Then the data were analyzed by data reduction, data display, conclusion drawing and verification. The results of this study indicate that the maxims obeyed by students are the maxim of wisdom, the maxim of praise, the maxim of generosity, the maxim of humility, and the maxim of sympathy. The maxim that is obeyed the most is the maxim of praise. Violations of the maxims in student speech are found in the maxim of wisdom, the maxim of praise, the maxim of generosity, and the maxim of humility. The maxim that is obeyed the most is the maxim of wisdom. Keywords: Javanese speech level; politeness principles; student politeness